2015
DOI: 10.4236/jtr.2015.32005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Sensitivities of Different PCR Assays for the Detection of Mycobacterium tuberculosis Complex Isolates from Five Regions of Cameroon

Abstract: The accurate diagnosis of tuberculosis caused by members of the Mycobacterium tuberculosis complex (MTBC) has remained a major challenge in clinical laboratories worldwide. Several studies have evaluated the use of highly specific in-house PCR assays targeting the IS6110, hupB, rpoB, oxyR, and IS1081 genes in the detection of MTBC species with reports on variable sensitivities depending on the geographical sourcing of isolates. In the present investigations, we evaluated the sensitivities of these PCR assays o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…It was positive in 44% samples with maximum positivity in sputum (70%) which is comparable as reported by Rodrigues C et al, and Rishi et al 13,14 PCR IS1081 has shown 93.1% sensitivity (with 95% confidential interval) which is similar as reported by Fidelis et al, and Fatolahzadeh B. 15,16 This study showed that MGIT culture was positive in 44(44%) specimens, whereas IS1081 PCR showed that 74 (74%) specimens were positive for Mycobacterium tuberculosis. The difference was found to be statistically significant (p <0.05).…”
Section: Discussionsupporting
confidence: 86%
“…It was positive in 44% samples with maximum positivity in sputum (70%) which is comparable as reported by Rodrigues C et al, and Rishi et al 13,14 PCR IS1081 has shown 93.1% sensitivity (with 95% confidential interval) which is similar as reported by Fidelis et al, and Fatolahzadeh B. 15,16 This study showed that MGIT culture was positive in 44(44%) specimens, whereas IS1081 PCR showed that 74 (74%) specimens were positive for Mycobacterium tuberculosis. The difference was found to be statistically significant (p <0.05).…”
Section: Discussionsupporting
confidence: 86%
“…It has been estimated that a rapid TB diagnostic test with at least 85% pooled sensitivity for smear-positive and smear-negative cases and 97% specificity could save approximately 400,000 lives annually [ 25 ]. This study determined the diagnostic accuracy of D-PCR using primers ( IS6110 and rpoB ) in direct sputum samples, hitherto established to be sensitive and specific [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, four false-negative PCR results were recorded; two smear-positive/culture-positive, one culture-positive/smear-negative and one clinically diagnosed TB case. False negativity in nucleic acid amplification (NAA) tests for sputum has always been linked to the presence of inhibitors (including high amounts of genomic DNA), and a low number of bacilli [ 13 , 14 ]. However, because only presumptive identification of isolates (no speciation) was done before PCR, the possibility of detecting species other than Mycobacterium tuberculosis complex cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations